Kabbalistic circles in Jerusalem (1896-1948) - Meir, Jonatan. (Aries Book Series, 2016)
This book endeavors to fill a lacuna in the literature on early twentieth-century kabbalah, namely the lack of a comprehensive account of the traditional kabbalah seminaries (Yeshivot) in Jerusalem from 1896 to 1948 as well as the various manifestations of kabbalah within traditional Jewish society. The foundations that were laid in the early twentieth century also paved the way for the contemporary blossoming of kabbalah in many and manifold circles. In this sense, retracing the pertinent developments in Palestine at the outset of the twentieth century is imperative not only for repairing the distorted picture of the past, but for understanding the ongoing surge in kabbalah study.